Textbook analyses on reasoning-and-proving: Significance and methodological challenges - Stylianides, G (2014)
The activity of 'reasoning-and-proving' can serve as a vehicle to mathematical sense making and is thus important for students' learning of mathematics at all levels of education. Yet, reasoning-and-proving does not receive appropriate attention in typical classroom practice, and many students face serious difficulties with it. One important, albeit underexplored and insufficiently exploited, leverage point for supporting classroom work on reasoning-and-proving is textbooks. As a first step towards a possible longer-term goal to develop textbooks that can appropriately support classroom work on reasoning-and-proving, it is necessary to understand how reasoning-and-proving is treated in existing textbooks and to grapple with the many methodological challenges that surround textbook analyses on reasoning-and-proving. © 2014.